Flotsam. - Wiesner, David (New York : : Clarion Books, 2006)
When a young boy discovers a camera on the beach and develops the film, he finds with his microscope many layers of pictures within the photographs
Caldecott 2007 Medal Winner
K-3
Keywords: Cameras--Juvenile fiction; Beaches--Juvenile fiction; Stories without words; Cameras--Fiction.; Beaches--Fiction.; wordless